Author Correction: Aberrant activation of non-coding RNA targets of transcriptional elongation complexes contributes to TDP-43 toxicity - Chia-Yu Chung (Nature Portfolio, 2019)
The original version of this Article contained an error in the author affiliations. The affiliation of Alice Chen-Plotkin with the Department of Neurology, Perelman School of Medicine, Philadelphia, PA, 19104 USA was inadvertently omitted. This has now been corrected in both the PDF and HTML versions of the Article.